Ultrasound assessment of endometrial thickness in women with endometrial bleeding - Ana Kocevska; Bashkim Ismaili; Kristina Skeparovska; Dimitar Georgiev; Mladen Risteski; Shenol Tahir (My University, 2022)
Objectives: Dysfunctional endometrial bleeding is often during the menopausal transition as a result of hormonal changes during this period. In postmenopaus, there should be no uterine bleeding. Postmenopausal bleeding occurs in approximately 90% of patients with endometrial cancer, but only 9% of women with postmenopausal bleeding have endometrial cancer. The aim of this study is to determine the histopathological changes of the endometrium that occur in women with perimenopausal and postmenopausal bleeding and the association with endometrial thickness and anteroposterior diameter of the uterus. Methods: This study involved 120 patients with fractionated explorative curettage due to abnormal uterine bleeding. The examined group was divided in two subgroups: 60 women in perimenopausis and 60 women in postmenopausis. Anamnestic data were taken from all respondents. Ultrasound measurement of anteroposterior diameter of uterus and endometrial thickness were made with endovaginal ultrasound probe. Results: The most common pathological change of the endometrium was an endometrial polyp (in 45% of the respondents). 26.7% of perimenopausal women had dysfunctional uterine bleeding. Endometrial adenocarcinoma was present in 3% of perimenopausal and in 5% of postmenopausal women. The average value of the anteroposterior diameter of the uterus was 50.7 mm in perimenopausal, 37.3 mm in postmenopausal group, and the difference of 13.4 mm was statistically significant (p < 0.0001). The average thickness of the endometrium was 13.6 mm in perimenopausal, 10.3 mm in postmenopausal group, and the difference of 3.3 mm was statistically significant (p = 0.00011). Conclusions: Fractionated explorative curettage is an effective method for timely and effective diagnosis of pathological changes of the endometrium in women with abnormal uterine bleeding Perimenopausal patients had significantly higher anteroposterior diameter of the uterus and thicker endometrium than those in the postmenopausal period.
Abstracts of the 32nd World Congress on Ultrasound in Obstetrics and Gynecology, 16–18 September 2022, London, UK & Virtual